Exploring the relationship between temperament traits, psychological symptoms, and functional disability assessed with the WHODAS 2.0 in persons with multiple sclerosis - Infortuna, Carmenrita; Buccafusca, Maria; Graceffa, Anita Maria Stella; Maiorana, Enrica; Wang, Ray; Ganesh, Siddarth; Yedidia, Orion; Bruno, Antonio; Iannuzzo, Fiammetta; Thomas, Florian P.; Battaglia, Fortunato (Frontiers in Neurology, 2025)
BackgroundThe relationship between psychological comorbidity and functional impairment in multiple sclerosis (MS) remains to be thoroughly investigated. This study examined the associations between temperament traits, psychological comorbidities, and disability as measured by the World Health Organization Disability Assessment Schedule (WHODAS) 2.0 in persons with Relapsing–Remitting Multiple Sclerosis (RRMS).MethodsIn this cross-sectional study, persons with RRMS underwent a comprehensive assessment of temperament profiles, psychological status, and functional disability. Assessment tools included the Depression Anxiety Stress Scale (DASS-21) and the Temperament Evaluation of Memphis, Pisa, Paris, and San Diego Autoquestionnaire (TEMPS-A) short form. Functional status was evaluated using the 36-item WHODAS 2.0. Multivariate regression analyses were performed to evaluate relationships between variables.ResultsThe study cohort comprised 105 persons with RRMS Hierarchical regression models showed that age and disease duration were significant predictors, with age positively associated with D02 and D06 dimensions, and disease duration linked to D02, D05, and D06 WHODAS 2.0 dimensions. Among temperament traits, hyperthymic temperament showed negative associations across multiple dimensions. Anxiety had strong positive association with disability. Model fit improved significantly with each step, with Step 3 explaining additional variance.ConclusionThese findings demonstrate significant associations between temperamental characteristics, particularly hyperthymic traits, −anxiety, and functional disability in persons with RRMS. Future research should investigate these relationships over time to understand causal links and create better treatments to slow disability progression. These findings could help improve how we assess and treat patients.